2015
DOI: 10.15171/ijoem.2015.632
|View full text |Cite
|
Sign up to set email alerts
|

Validity and Reliability of Malay Version of the Job Content Questionnaire among Public Hospital Female Nurses in Malaysia

Abstract: The M-JCQ is a reliable and valid instrument to measure psychosocial and physical stressors in the workplace of public hospital nurses in Malaysia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 26 publications
2
22
1
Order By: Relevance
“…The psychological job demands scale had an unacceptable level of internal consistency (0.48). The psychological job demands scale, especially the one with five questions, tends to have borderline alpha values, but there are some studies that show completely inadequate values (Amin, Quek, Oxley, Noah, & Nordin, 2015;Araújo, & Karasek, 2008;Hadi, Naing, Daud, & Nordin, 2006;Li et al, 2004;Mausner-Dorsch, & Eaton, 2000;Phakthongsuk, & Apakupakul, 2008). Karasek et al (1998) reviewed six studies from America, Europe and Asia and concluded that, indeed, the psychological job demands scale, with five questions, showed poor internal consistency.…”
Section: Discussionmentioning
confidence: 99%
“…The psychological job demands scale had an unacceptable level of internal consistency (0.48). The psychological job demands scale, especially the one with five questions, tends to have borderline alpha values, but there are some studies that show completely inadequate values (Amin, Quek, Oxley, Noah, & Nordin, 2015;Araújo, & Karasek, 2008;Hadi, Naing, Daud, & Nordin, 2006;Li et al, 2004;Mausner-Dorsch, & Eaton, 2000;Phakthongsuk, & Apakupakul, 2008). Karasek et al (1998) reviewed six studies from America, Europe and Asia and concluded that, indeed, the psychological job demands scale, with five questions, showed poor internal consistency.…”
Section: Discussionmentioning
confidence: 99%
“…Decision authority was assessed using three Malay‐translated items adapted from the decision authority subscale of the Job Content Questionnaire (Karasek et al ., ). Good reliability and validity has been shown in Malaysian work setting (Amin, Quek, Oxley, Noah, & Nordin, ; Edimansyah, Rusli, Naing, & Mazalisah, ). An example item is as follows: ‘On my job, I have very little freedom to decide how I do my work’.…”
Section: Methodsmentioning
confidence: 99%
“…Validation studies for the JCQ in some countries, such as Malaysia, the Islamic Republic of Iran, China, and Spain, were conducted with nurses as study participants. [19][20][21][22] Korean and Greek versions were developed for hospital medical staff, but not restricted to nurses. 23,24 While JCQ has been widely used internationally in medical settings, research using JCQ is still limited LMICs in South-East Asia, especially low-and lower middle-income countries.…”
Section: Introductionmentioning
confidence: 99%